SOIL FERTILITY FORMATION UNDER ORGANIC FARMING - Pysarenko, V. M.; Pysarenko, P. V.; Pysarenko, V. V.; Gorb, O. O.; Chaіka, T. O. (Scientific Progress & Innovations, 2019)
Modern understanding of forming plant nutritive regime under the conditions of organic farming is pre-sented. This understanding is based on the creation of agro-ecosystems, which are maximally close to natu-ral formations owing to regulating two global processes – photosynthesis and nitrogen fixation in all their manifestations. It is substantiated that nitrogen is not only a basic biogenic element of the living matter, per-forming the most important role in the life of plants and animals, but also it is the leading element of arable farming. The influence of nodule-forming bacteria on soil enrichment with nitrogen for cultivating various plants and forming grain productivity was analyzed, which is necessary to take into account while determin-ing the rates of nitrogen fertilizers (under intensive farming). It was determined that organic fertilizers are another important factor of optimizing crops’ nutritive regime in organic farming. The application of such fertilizers assists in activating the activity of soil micro-flora, and after their mineralization the saturation of the soil with nutrients used by plants takes place. It was established that green manure crops are also one of factors in forming crop nutritive regime as inexhaustible and constantly renewable source of organic matter. It was also mentioned that using green manure crops favors including unused reserves of phosphorus, potas-sium, calcium, magnesium and other plant nutrients in small circulation from deeper genetic horizons of the soil. It was noted that systemic cultivation of perennial and annual legume grasses, green manure crops and application of manure as elements of organic farming technologies, considering their after-effect, practically ensures the recommended mineral nutrient regime of the main crops. It is stated that plants’ nutritive regime is also considerably influenced by earthworm coprolites, which improve soil nutritive regime, its structure, and physical properties. It is proved that organic fertilizers are one of the reserves for replenishing the con-tent of carbon dioxide in the atmosphere ground layer, which is very important for photosynthesis and, final-ly, for the formation of crop productivity. The collected information can be used in researches, introduced in production, educational process at training specialists in the field of knowledge 20 “Agrarian sciences and food”.